"After the Storms: Reflections on the US Virgin Islands". Issue 2 (24th September 2018) - Navarro, Tami
Abstract: This essay explores the impact of Hurricanes Irma and Maria on the American‐owned islands of St. Croix, St. Thomas, and St. John. It details the ambivalence with which the US engages with the Virgin Islands (given the regular elision of these islands from the category of "United States" in media coverage and by US government officials), as well as the ways in which these storms have revealed and brought to the fore long‐standing tensions in relation to the ways the islands relate both to each other and to the United States. In particular, there have been renewed tensions between St. Thomas and St. Croix around federal relief funding and awareness of conditions on the ground.